Barley-Pearl Millet-Milk based Complementary Food: Steady and Dynamic Oscillatory Rheology and Application of Modified Cox-Merz Rule - C.T., Manoj Kumar; Panjagari, Narender Raju; Singh, Ashish Kumar; Minz, Prashanth Saurabh (Indian Journal of Dairy Science, 2016)
The rheological behaviour of a novel barley-pearl millet-milk based complementary food was studied by both steady shear and dynamic oscillatory methods and the influence of the usual reconstitution temperatures (20-80°C) on their flow and visco-elastic properties were analysed. The steady shear test revealed that shear stress decreased with an increase in the temperature. Hershel Bulkey model was found to best fit the experimental data. Further, the model parameters such as flow behaviour and consistency indices were found to decrease with an increase in temperature. The consistency index value was found to reach equillibrium after 50°C. The values of flow behaviour index indicated shear thinning behaviour of the product. However, the yield stress didn’t showed any temperature dependency. The dynamic oscillatory tests revealed that the G¢ was found to be higher than G² and both were found to increase with an increase in angular frequency indicating a strong viscoelastic behaviour. Samples showed increasing damping factor values with frequency indicating higher contribution of the viscous component at higher frequencies. The great loss in elasticity and increment in viscosity with increase in temperature showed that the product behaved more liquid in consistency. The power law model could describe the frequency dependence of G¢ and G². The modified Cox-Merz rule fitted well upon insertion of shift factor.